Antibacterial Activity of Streptomyces SAE4034 Isolated from Segara Anakan Mangrove Rhizosphere against Antibiotic Resistant Bacteria - Dini Ryandini; Hendro Pramono; Sukanto Sukanto (Biosaintifika: Journal of Biology & Biology Education, 2018)
Actinomycetes SAE4034 isolates was isolated from Rhizophora apiculata rhizosphere mud showed some antibacterial properties. The antibacterial ability of this isolate has not been tested on antibiotic resistant bacterial pathogens. However, there was no research has been reported regarding actinomycetes from Segara Anakan mangrove area resulting compounds inhibit the growth of antibiotics-resistant bacteria. Therefore, it is important to investigate its capability against antibiotics resistant bacteria or multi drug resistant bacteria (MDR bacteria). The research aimed to know the ability of actinomycetes SAE4034 in inhibit MDR bacteria and to identify the species profiles. The research methods included isolate characterization involving morphology, physiology/enzymatic and molecular properties. MDR bacterial inhibition assay, antibacterial compound extraction and antibacterial compound test using thin layer chromatography (TLC) method, observation of morphological and biochemical properties, DNA isolation, amplification and analysis of 16SrRNA sequence, and phylogeny tree analysis. The methods of this study included MDR anti-bacterial assay and antibacterial compound test. Subsequent step was isolate characterization including observation of morphological and physiological / enzymatic properties, and 16S rRNA gene sequence. The results showed that culture extract was able to inhibit the growth of MDR bacteria i.e. Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterococcus sp., but no inhibition to Enterobacter cloacae. The bioactive compound showed 4 spots with Rf values of 0.36; 0.45; 0.54; and 0.6. Based on morphology, physiology / enzymatic and 16S rRNA gene sequences characteristics, actinomycetes SAE4034 isolate is Streptomyces sp. This research showed new Streptomyces strain that serves as a source of MDR antibacterial compounds and useful in development of antibiotic for combating infectious diseases caused by MDR bacteria